PERAN DIGITAL MARKETING DALAM PENGEMBANGAN DESA WISATA DI KABUPATEN TABANAN - Putu Widya Darmayanti; I Made Darma Oka; Fransiska Fila Hidayana (Jurnal Kajian dan Terapan Pariwisata, 2023)
This article examines the role of digital marketing in the development of tourist villages. This research uses qualitative data. Collecting data using in-depth interviews with community leaders. Data analysis used qualitative data analysis techniques. The results showed that the role of digital marketing in tourist villages makes big contribution to influences the sustainability of tourist villages. The development of digital marketing is able to have positive impact in introducing and promoting tourism villages. The application of digital marketing carried out by each tourism can be an opportunity for the number of tourist visits. It is recommended that the tourism stakeholders must synergize to the development of the tourism village remains sustainable.